Attributing Changing Rates of Temperature Record Breaking to Anthropogenic Influences. Issue 11 (23rd November 2017) - King, Andrew D.
Abstract: Record‐breaking temperatures attract attention from the media, so understanding how and why the rate of record breaking is changing may be useful in communicating the effects of climate change. A simple methodology designed for estimating the anthropogenic influence on rates of record breaking in a given time series is proposed here. The frequency of hot and cold record‐breaking temperature occurrences is shown to be changing due to the anthropogenic influence on the climate. Using ensembles of model simulations with and without human‐induced forcings, it is demonstrated that the effect of climate change on global record‐breaking temperatures can be detected as far back as the 1930s. On local scales, a climate change signal is detected more recently at most locations. The anthropogenic influence on the increased occurrence of hot record‐breaking temperatures is clearer than it is for the decreased occurrence of cold records. The approach proposed here could be applied in rapid attribution studies of record extremes to quantify the influence of climate change on the rate of record breaking in addition to the climate anomaly being studied. This application is demonstrated for the global temperature record of 2016 and the Central England temperature record in 2014. Key Points: A method for assessing anthropogenic influence on rates of record‐breaking and recent records is presented. Climate change has increased the likelihood of global temperature record‐breaking occurrences since the 1960s. Anthropogenic influences have increased the probability of recent records being broken ‐ such as the global annual temperature of 2016. Plain Language Summary: Recently we have seen more record‐breaking temperatures being set both globally and locally. This study provides a methodology for quantifying the human influence on the changing rate of record‐breaking. Using climate model simulations with and without human influences the likelihood of setting new records can be compared. I find that climate change has been increasing the likelihood of global temperature record occurrences since the 1960s. The chance of new warm records being set, like the 2016 global temperature record and the 2014 Central England temperature record, have increased and this can be attributed to the human influence on the climate.